Hot restoration technologies for external coating tiles: Nossa Senhora da Soledade Cemetery (Belém, Brazil) - Mendes,Stephanie Assef (2017)
Abstract In Belém, Brazil, during the 19th century, Portuguese tiles were used for the external facing of sepultures at the Soledade Cemetery. These pieces are fragile because of exposure to the tropical climate and of their location close to the ground. This research aims to obtain subsidies for the restoration of the glazed layer, through hot restoration, to serve as theoretical and technological references for future restoration projects. The samples consisted of fragments of Portuguese historical tiles from the Soledade Cemetery. Restoration was performed by cleaning (both mechanical and chemical ways) and re-firing (1000ºC). Before and after the re-firing, samples were submitted to the analytical technique of X-ray diffraction. The results indicate that the re-firing eliminated defects and pathologies existent in the glaze and caused changes in the mineralogical composition of the ceramics. Used carefully, the hot technique is one of the alternatives to improve durability and protect the Soledade historical tiles.